Neutrophil‐to‐lymphocyte ratio is associated with malnutrition risk estimated by the Royal Free Hospital–Nutritional Prioritizing Tool in hospitalized cirrhosis. Issue 1 (20th April 2021) - Wang, Xiaoyu; Feng, Hongjuan; Hui, Yangyang; Yu, Zihan; Zhao, Tianming; Mao, Lihong; Lin, Lin; Wang, Bangmao; Fan, Xiaofei; Yu, Qingxiang; Sun, Chao
Abstract: Background: Liver cirrhosis is characterized by immune dysfunction, contributing to malnutrition. We previously revealed neutrophil‐to‐lymphocyte ratio (NLR) as an indicator of disordered immune system. Herein we aimed to (1) determine the optimal NLR cutoff that best predicts malnutrition risk and (2) clarify the association between NLR and nutrition status. Methods: A total of 135 hospitalized patients with cirrhosis were included. Immune dysfunction was evaluated by levels of serum C‐reactive protein (CRP), NLR, and other parameters. Malnutrition was screened by a risk score referring to the Royal Free Hospital–Nutritional Prioritizing Tool (RFH‐NPT). Receiver operating characteristic (ROC) curve was implemented to determine the best NLR cutoff that predicts malnutrition risk. Correlation between NLR and indicators of hepatic and physical function (handgrip strength) were also examined. Multivariable logistic regression was used to assess the association between NLR and malnutrition risk. Results: ROC curve revealed that the optimum cutoff to predict malnutrition risk was NLR > 4.2, with a sensitivity of 47.2%, specificity of 81.0%, negative predictive value of 58.0%, and positive predictive value of 74.5%, respectively. Patients with NLR > 4.2 exhibited a higher RFH‐NPT score, serum platelet‐to‐lymphocyte ratio, and CRP. A positive correlation was found between NLR values and Child‐Turcotte‐Pugh ( r = 0.22; P = .010), model for end‐stage liver disease ( r = 0.36; P < .001), and RFH‐NPT scores ( r = 0.31; P < .001). NLR was a risk factor for malnutrition independently of alcoholic liver disease and presence of ascites. Conclusions: Immune dysfunction measured by NLR was associated with malnutrition risk estimated by RFH‐NPT in cirrhosis.